Whither wilderness? An investigation of technology use by long‐distance backpackers. (18th December 2020) - Hyatt, Ed; Harvey, Morgan; Pointon, Matthew; Innocenti, Perla
Abstract: The popular outdoor pursuit of backpacking is profoundly changing as the community embraces contemporary information technologies. However, there is little empirical evidence on the adoption and use of consumer electronics by backpackers, nor the implications this has for their habits, practices, and interactions. We investigate long‐distance backpackers' articulations with mobile information technology during the TGO Challenge, a coast‐to‐coast crossing of the Scottish Highlands. By employing mixed methods, we explore how and why backpackers use such technology when planning and undertaking their journeys via a survey ( n = 116), pre‐ and post‐challenge interviews with selected TGO participants, and daily in‐field video‐logs. Our results suggest many advantages to using technology in this context, including fluidity of communications and access, while noting that reliance on technology is leading to issues such as increased need for battery power management, and deskilling. The findings highlight implications for the juxtaposition between outdoor recreation, information behavior, and human computer interaction (HCI) and suggest future work in this area.